2021
DOI: 10.1186/s12888-021-03392-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for non-suicidal self-injury among patients with depression or bipolar disorder in China

Abstract: Backgrounds Non-suicidal self-injury is a serious health problem among patients with depression or bipolar disorder. However, few studies within the Chinese context have investigated the prevalence of NSSI and its risk factors in above populations. The purpose of this study was to investigate the prevalence of non-suicidal self-injury and its risk factors in patients with depression or bipolar disorder in China. Methods The final sample comprised o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 60 publications
3
38
1
5
Order By: Relevance
“…In our study, the prevalence of NSSI was over forty percent; girls had higher rates of NSSI, and depressive disorder was the primary psychiatric diagnosis. This is consistent with characteristics in previous adolescent samples [ 4 , 35 , 36 ]. Women were more likely to engage in NSSI than men in clinical samples [ 4 ], especially adolescent girls (16–19 years old) [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the prevalence of NSSI was over forty percent; girls had higher rates of NSSI, and depressive disorder was the primary psychiatric diagnosis. This is consistent with characteristics in previous adolescent samples [ 4 , 35 , 36 ]. Women were more likely to engage in NSSI than men in clinical samples [ 4 ], especially adolescent girls (16–19 years old) [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Most self-injurers cut themselves using a sharp object, such as a knife or blade, mainly on the forearms, legs, and/or abdomen (29), which was consistent with our research. Studies con rmed that life stressors and adverse interpersonal experiences are associated with an increased risk of NSSI (30,31), which is consistent with the present result. In the present study, we also found that sleep problems were most common in the BD (NSSI) group than in the BD (non-NSSI) group or healthy group.…”
Section: Discussionsupporting
confidence: 92%
“…Elbogen EB et al demonstrates that substance abuse, environmental stressors, and history of violence were associated with risky behaviors of BD [17]. Some studies also indicated that younger age [18,19,6,20], lacking of insight of BD [21][22][23][24] and mental dysfunction [25][26][27] might make BD patients to be more aggressive.…”
Section: Introductionmentioning
confidence: 99%